Assessment of Shading Systems with Advanced Windows at Restaurants Under Sunny Climates in Spain - Urtza Uriarte; Olatz Irulegi; Rufino J. Hernández (Buildings)
This study addresses daylighting to enhance the quality of indoor atmospheres, considering building skins. In the hotel industry, lighting accounts for more than 10% of energy consumption. Many highly glazed façades create visual comfort problems, resulting in increased electric lighting consumption. Ninety-four restaurants were studied in Spain; almost all cases have a window with outside views, and more than half of the cases have tables adjacent to the outside views. However, it is difficult to balance daylight use, a shading system, and the outside view. A virtual restaurant prototype is built by Rhinoceros to simulate the daylight glare index by Evalglare and daylight autonomy of a highly glazed façade with three different shading systems by Radiance through a screen and an overhang with and without a complex fenestration system. The results show that the screen system reduces the daylight glare index value to imperceptible glare (15%), while the daylight glare index for the overhang with and without a complex fenestration system increases to acceptable glare (21%). However, the daylight autonomy for the screen system is almost half (52%) the daylight autonomy for the overhang systems (95%). Although the daylight glare index for the overhang with a complex fenestration system is slightly higher, the illuminance level and its distribution performance are better without obstructing the outdoor view.